1H NMR-based metabolomics for the discrimination of celery (Apium graveolens L. var. dulce) from different geographical origins. (1st December 2020) - Lau, Hazel; Laserna, Anna Karen Carrasco; Li, Sam Fong Yau
Highlights: NMR-based metabolomics was evaluated for celery origin discrimination. Untargeted and targeted metabolomics resulted in complementary findings. Key metabolite classes differentiating origins include sugars, amino and organic acids. Mannitol was identified as the primary discriminator for geographical origin. NMR-based metabolomics enabled identification of biomarkers of geographical origins. Abstract: Celery ( Apium graveolens L. var dulce) is a widely cultivated vegetable which is popularly consumed due to its nutrient content and contains bioactive metabolites with positive effects on human physiology. In this study, 1 H NMR spectroscopy coupled with multivariate statistical analyses was used to distinguish celery stem and leaf samples from different geographical origins. Principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA) were employed to investigate the differences between celery extracts from three geographical origins: Australia, Taiwan and China. Sugars, amino acids and organic acids were found to contribute significantly to the differentiation between origins, with mannitol identified as an important discriminating metabolite. It was demonstrated that NMR-based metabolomics is an effective approach for establishing reliable metabolomic fingerprints and profiles, enabling the identification of metabolite biomarkers for the possible discrimination of geographical origin.